2004
DOI: 10.1182/blood-2004-03-0982
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative radiochemotherapy followed by autologous stem cell transplantation in first remission prolongs progression-free survival in follicular lymphoma: results of a prospective, randomized trial of the German Low-Grade Lymphoma Study Group

Abstract: Conventional chemotherapy has failed to substantially prolong survival for patients with advanced follicular lymphoma. To improve outcomes, the German LowGrade Lymphoma Study Group (GLSG) initiated a randomized trial to compare the effect of potentially curative myeloablative radiochemotherapy followed by autologous stem cell transplantation (ASCT) with interferon-␣ (IFN-␣) maintenance therapy in first remission. Three hundred seven patients (younger than 60 years) with follicular lymphoma were recruited into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
2
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(164 citation statements)
references
References 27 publications
1
153
2
8
Order By: Relevance
“…We have only included patients undergoing transplantation beyond first response, as this is the currently accepted indication for transplantation in FL. [18][19][20] A prospective study comparing auto-SCT with RIST in this setting unfortunately failed due to poor accrual, 16 and further prospective comparative studies in this setting are unlikely to be performed. Therefore, retrospective studies describing these two forms of transplant provide an important source of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have only included patients undergoing transplantation beyond first response, as this is the currently accepted indication for transplantation in FL. [18][19][20] A prospective study comparing auto-SCT with RIST in this setting unfortunately failed due to poor accrual, 16 and further prospective comparative studies in this setting are unlikely to be performed. Therefore, retrospective studies describing these two forms of transplant provide an important source of data.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] By contrast, auto-SCT is associated with a low early NRM of o5%. 2,3,[18][19][20] Late toxicities must also be taken into consideration when selecting a transplant strategy. Thus following an auto-SCT the development of secondary MDS (myelodysplastic syndrome)/AML has been reported in up to 10% of patients at 10 years post transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with FL are normally not considered candidates for an autologous HSCT as first-line therapy, although three phase III prospective clinical trials [47][48][49] performed before the 'rituximab era' suggested a role in some subgroups of high-risk patients. Autologous HSCT remains the standard approach for early relapsing patients with FL.…”
Section: Follicular Lymphomamentioning
confidence: 99%
“…Most of the randomized trials of NHL including an ASCT arm have accepted only patients less than 60 years of age, [9][10][11][12] although patients up to 65 years have been included in more recent trials. 13,14 In MM, the upper age limit in randomized trials has shifted from 60 15,16 to 65 years.…”
Section: Who Is Elderly?mentioning
confidence: 99%